Potent Tau Aggregation Inhibitor D‐Peptides Selected against Tau‐Repeat 2 Using Mirror Image Phage Display. (12th September 2021) - Malhis, Marwa; Kaniyappan, Senthilvelrajan; Aillaud, Isabelle; Chandupatla, Ram Reddy; Ramirez, Lisa Marie; Zweckstetter, Markus; Horn, Anselm H. C.; Mandelkow, Eckhard; Sticht, Heinrich; Funke, Susanne Aileen
Abstract: Alzheimer's disease and other Tauopathies are associated with neurofibrillary tangles composed of Tau protein, as well as toxic Tau oligomers. Therefore, inhibitors of pathological Tau aggregation are potentially useful candidates for future therapies targeting Tauopathies. Two hexapeptides within Tau, designated PHF6* (275‐VQIINK‐280) and PHF6 (306‐VQIVYK‐311), are known to promote Tau aggregation. Recently, the PHF6* segment has been described as the more potent driver of Tau aggregation. We therefore employed mirror‐image phage display with a large peptide library to identify PHF6* fibril binding peptides consisting of D‐enantiomeric amino acids. The suitability of D‐enantiomeric peptides for in vivo applications, which are protease stable and less immunogenic than L‐peptides, has already been demonstrated. The identified D‐enantiomeric peptide MMD3 and its retro‐inverso form, designated MMD3rev, inhibited in vitro fibrillization of the PHF6* peptide, the repeat domain of Tau as well as full‐length Tau. Dynamic light scattering, pelleting assays and atomic force microscopy demonstrated that MMD3 prevents the formation of tau β‐sheet‐rich fibrils by diverting Tau into large amorphous aggregates. NMR data suggest that the D‐enantiomeric peptides bound to Tau monomers with rather low affinity, but ELISA (enzyme‐linked immunosorbent assay) data demonstrated binding to PHF6* and full length Tau fibrils. In addition, molecular insight into the binding mode of MMD3 to PHF6* fibrils were gained by in silico modelling. The identified PHF6*‐targeting peptides were able to penetrate cells. The study establishes PHF6* fibril binding peptides consisting of D‐enantiomeric amino acids as potential molecules for therapeutic and diagnostic applications in AD research. Abstract : Alzheimer's disease and other Tauopathies are associated with neurofibrillary tangles composed of Tau protein, as well as toxic Tau oligomers. Inhibitors of pathological Tau aggregation are potentially useful candidates for future therapies targeting Tauopathies. We employed mirror‐image phage display with a large peptide library to identify Tau binding peptides consisting of D‐enantiomeric amino acids. The suitability of D‐enantiomeric peptides for in vivo applications, which are protease stable and less immunogenic than L‐peptides, has already been demonstrated. The identified D‐enantiomeric peptides prevent the formation of β‐sheet‐rich Tau fibrils by diverting Tau into large amorphous aggregates. They might be interesting for AD therapy.